A systemic study on the effect of egg white protein and isomalto‐oligosaccharide mixture on the functional and gelation properties of Culter alburnus myofibrillar protein during long‐term frozen storage. (3rd November 2022) - Zhang, Zhongli; Xiong, Zhouyi; Xiong, Hanguo; Walayat, Noman; Nawaz, Asad; Khalifa, Ibrahim; Aadil, Rana Muhammad; Li, Sha; Lorenzo Rodriguez, Jose M.
Summary: The protective effects of egg white protein (EWP) and isomalto‐oligosaccharide (IMO) mixture (EWP/IMO, 1:1, m/m) on Culter alburnus myofibrillar proteins (Mfp) during long‐term frozen storage were systemically evaluated by comparing Mfp samples treated with EWP/IMO, IMO or EWP alone, using sample without any of them as blank control. After long‐term frozen storage, 1% IMO and 1% EWP/IMO were more effective than 1% EWP in reducing oxidative denaturation‐induced changes in functional groups and conformational sites of Mfp. Additionally, after frozen storage for 60 days, Mfp emulsion activity index (EAI) and emulsion stability index (ESI) were significantly ( P  < 0.05) higher in 1% IMO (20.68 m 2  g −1 vs. 56.54%) and 1% EWP/IMO (18.47 m 2  g −1 vs. 53.09%) than in 1% EWP (16.73 m 2  g −1 vs. 45.98%) and blank control (15.16 m 2  g −1 vs. 40.13%). Furthermore, Mfp gel strength was significantly ( P  < 0.05) higher in 1% EWP/IMO (7.14 g cm −1 ) than in IMO (6.33 g cm −1 ), EWP (5.34 g cm −1 ) and blank control (4.58 g cm −1 ). Moreover, rheological test and LF‐NMR results showed that adding EWP/IMO could more effectively improve Mfp gel viscoelasticity and three‐dimensional gel network than adding EWP or IMO alone. This study provides a new theoretical perspective for applying EWP/IMO as a potential low‐temperature protective agent in protein‐based gel products . Abstract : The protective effects of egg white protein (EWP) and isomalto‐oligosaccharide (IMO) mixture on Culter alburnus myofibrillar proteins (Mfp) during long‐term frozen storage by comparing Mfp samples treated with EWP/IMO, IMO or EWP alone, using sample without any of them as blank control, which systemically evaluated though the functional groups, conformation sites, emulsifying ability and gelation properties of Mfp.